Zabawy i zabawki dziecięce w drugiej połowie XIX i na początku XX wieku – wybrane problemy z wykorzystaniem grafik z epoki - Nawrot-Borowska, Monika (Poznańskie Towarzystwo Przyjaciół Nauk we współpracy z Zakładem Historii Wychowania, WSE UAM, 2013)
The aim of the article is to present aspects of selected games and children’s toys in the second half of the nineteenth and early twentieth centuries. The inspiration for the consideration will be graphics from the press and (mainly children’s) literature of the period, accompanied by a description of the games and toys presented in them. The sources providing the graphics will be educational literature and guides, and guides to the health and hygiene of children and teenagers. These texts can be useful in studying history, whether in the classroom or during seminars on the history of education.
Games and children’s toys in the second half of the nineteenth and early twentieth centuries – selected aspects of using graphics from the period
Keywords: fun; toy; childhood; 19th century; iconography